2021
DOI: 10.1002/hep.31984
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Course and Risk Factors for Infection in Severe Forms of Alcohol‐Associated Liver Disease

Abstract: BaCKgRoUND aND aIMS:Infection is a major driver of mortality in patients with advanced alcohol-associated liver disease (ALD). The epidemiology and clinical course of patients infected with life-threatening forms of ALD, including severe alcohol-associated hepatitis (sAH) and decompensated alcohol-associated cirrhosis (DAC), and specific risk factors for infection remain mostly unknown. appRoaCH aND ReSUltS:In this observational study, we assessed all infectious episodes occurring within a 90-day period from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…30 Several studies have demonstrated increased risk of infection among patients with AH treated with corticosteroids. 10,13,31,32 In the STOPAH trial, prednisolone nearly doubled the risk of infections reported as serious adverse events in patients with AH (13% vs. 7%, p=0.002). 10 In a post-hoc analysis that the STOPAH trial used to evaluate bacterial DNA levels to monitor for infection, it was noted that patients with sAH who were given prednisolone were at greater risk for developing serious infections compared to those who did not receive prednisolone.…”
Section: Corticosteroid-related Immunosuppressionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Several studies have demonstrated increased risk of infection among patients with AH treated with corticosteroids. 10,13,31,32 In the STOPAH trial, prednisolone nearly doubled the risk of infections reported as serious adverse events in patients with AH (13% vs. 7%, p=0.002). 10 In a post-hoc analysis that the STOPAH trial used to evaluate bacterial DNA levels to monitor for infection, it was noted that patients with sAH who were given prednisolone were at greater risk for developing serious infections compared to those who did not receive prednisolone.…”
Section: Corticosteroid-related Immunosuppressionmentioning
confidence: 99%
“…31 Another observational study showed that corticosteroid use, along with younger age and higher MELD score, were independently associated with infection, specifically invasive fungal infections (IFIs). 32 However, separate studies have indicated that corticosteroids do not appear to increase the risk of infections in those with sAH, but rather the lack of response to corticosteroids may indicate greater risk of infection. A prospective study by Louvet et al 33 analyzed a cohort of 246 patients and found that the infection risk was significantly greater in steroid non-responders compared to responders, at 42.5% vs. 11.1%, respectively (p<0.000001).…”
Section: Corticosteroid-related Immunosuppressionmentioning
confidence: 99%
“…Cirrhotic patients represents 2–5% [ 5 ] of all patients in intensive care units (ICUs). Digestive hemorrhage and sepsis are the main causes leading to ICU hospitalization [ 6 ]. Mechanical ventilation is often required in this setting and can lead to the development of VAP.…”
Section: Introductionmentioning
confidence: 99%
“…The type, timing, and severity of infection overall, before, after, and with regard to corticosteroid response, are described in detail in our article. ( 1 )…”
mentioning
confidence: 99%
“…We appreciate the interest in our article recently published in Hepatology , which gives us the opportunity to further discuss our findings. ( 1 )…”
mentioning
confidence: 99%